La recherche-action au service d’un changement organisationnel : l’expérience d’une équipe interprofessionnelle en lien avec le climat de sécurité perçu par les élèves - Carpentier, Geneviève; Villeneuve-Lapointe, Myriam; Sirard, Anick; Tardif, Catherine (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
As part of an action research project, sensitive data on the perception of safety climate were presented to an interprofessional team. Two guided reflective practices were implemented to support this team in the different stages of an organizational change. The thematic analysis of these two reflective practices allows us to highlight the themes addressed by the participants. First, the themes that emerged during the first practice were mainly related to external factors and to some possible solutions concerning only a few students. Then, during the second practice, professional readings and the accompanying guidance posture led the participants to broaden their discussions and propose possible solutions targeting all the students in the school.